1989
DOI: 10.1103/physrevb.39.1302
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium diffusion and magnetic resonance investigations inLiTaO3single crystals

Abstract: The diffusion coefficients of deuterium in single crystals of LiTaO& have been measured by rnonitoring the growth of OD infrared-absorption bands in samples heated in Aowing D20 vapor. At 950 K, the diffusion coe%cient is 1.7X 10 cm /s for diffusion along the crystallographic c axis, and the activation energy is 1.5 eV. Electric-field-enhanced diffusion of deuterium was also demonstrated. Proton replacement and electron-nuclear double resonance experiments have shown that the structure previously reported in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Different from O-D a , O-D b was observed even in experiments without irradiation [15][16][17], which suggest that the irradiation defects are not required for its formation. It has been reported that the proton of the O-H bond corresponding to O-D b lies only 0.02 nm below the oxygen plane (along the c axis) at a distance of 0.1 nm from the corresponding oxygen atom [18].…”
Section: Attributions Of O-d a And O-d Bmentioning
confidence: 60%
See 1 more Smart Citation
“…Different from O-D a , O-D b was observed even in experiments without irradiation [15][16][17], which suggest that the irradiation defects are not required for its formation. It has been reported that the proton of the O-H bond corresponding to O-D b lies only 0.02 nm below the oxygen plane (along the c axis) at a distance of 0.1 nm from the corresponding oxygen atom [18].…”
Section: Attributions Of O-d a And O-d Bmentioning
confidence: 60%
“…In this case, the formation of O-D a and O-D b has been ascribed to the isotope substitution between tritium induced by neutron irradiation and deuterium in D 2 O. O-D b has been indicated by a sharp and predominant peak while O-D a only by a very small peak [14]. On the other hand, if neutron irradiation was not conducted and deuterium was thermally introduced from D 2 O vapor, only O-D b was observed in LiNbO 3 [15] and LiTaO 3 [16,17]. The fact that O-D a was not observed in un-irradiated LiNbO 3 and LiTaO 3 in these experiments indicates that O-D a correlates with certain irradiation defects.…”
Section: Attributions Of O-d a And O-d Bmentioning
confidence: 90%
“…to studying the diffusion of hydrogen isotopes in nonmetallic Infrared-absorption data were taken with a spectrophotomesolids. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Hydrogen and its isotopes, deuterium and tritium, ter (Model 2000 FT-IR, Perkin-Elmer, Norwalk, CT). Measurediffuse much more slowly in insulators than in metals.ments of the intensity of the OH Ϫ (OD Ϫ ) band as a function of Although some metals are suitable for hydrogen-storage applilight polarization were made using a wire-grid silver bromide cations, the usefulness of ceramics is in their low permeability polarizer.…”
mentioning
confidence: 99%
“…The absorption occurring near 3500 cm --1 corresponds to the well-known infrared absorption bands of the OH -stretching vibration in ABO 3 and TB type crystals[7][8][9][10][11]. The as-grown KLN-2 crystals show a broad absorption peak near 3500 cm --1 and have an absorption coefficient of 1 cm --1 at peak position.…”
mentioning
confidence: 86%